The History of Insecurity: Exploring the Resilience and Agency of Women and Children in the World Conflict Zones - Monteh, René Ngek (Advances in Social Sciences Research Journal, 2025)
This article provides an in-depth examination of the complex and multifaceted history of insecurity faced by women and children in conflict zones worldwide. This research employs both a qualitative and a quantitative methodology, combining a comprehensive review of existing literature with in-depth case studies of women and children in conflict zones in the world. Through a critical analysis of historical and contemporary conflicts, this research reveals the disproportionate impact of violence, displacement, and human rights abuses on women and children. Despite these overwhelming challenges, women and children have consistently demonstrated remarkable resilience and agency, advocating for peace, justice, and human rights. This article concludes that women and children are critical actors in promoting peace and security in conflict zones. Their resilience and agency are essential in advocating for peace, justice, and human rights. Therefore, it is crucial to recognise and support their efforts, ensuring that their voices are heard and their rights are protected.